Multimodal input in the foreign language classroom: the use of hand gesture to teach morphology in L2 Spanish - Feijoo, Sara; Anglada, Mariona (Frontiers in Communication, 2024)
Many studies describe the benefits of morphological awareness in reading comprehension in both first and second languages. In turn, several studies demonstrate the positive impact of multimodal input while learning. In this study, we looked for a relationship between multimodal input, gesture in particular, and the development of morphological awareness in L2 Spanish. An experiment was carried out with 38 students of L2 Spanish, aged between 14 and 16, from a secondary school in the UK. The experiment consisted of a pretest and a posttest of morphological awareness mediating three sessions of training. During the training sessions, the participants were divided into 4 groups with different input modalities: audiovisual, audiovisual with text enhancement, audiovisual-gestural and control. Participants worked on a series of words with a morphemic component through the visualization of videos. The experiment provided significant results in terms of learning from pre-to post-test in one of the groups, the audiovisual-gestural group. Hence, we conclude that, in the short term, this type of training might have a positive impact on the development of morphological awareness.